2019
DOI: 10.1590/0103-8478cr20180561
|View full text |Cite
|
Sign up to set email alerts
|

Family farming and school meals in Rio Grande do Sul, Brazil

Abstract: In Brazil, at least 30% of the total financial resources provided by the federal government for school feeding should be used to buy products from family farming. The present study examines the profile of the purchase of these products in municipalities of the state of Rio Grande do Sul (RS), south Brazil, in 2014. A cross-sectional descriptive study was carried out with information obtained through a questionnaire sent to the municipalities and filled by respondents. Of the 371 participating municipalities, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
(35 reference statements)
0
2
0
11
Order By: Relevance
“…The availability of food from family farms was highlighted as one of the major criteria in 5 of the 21 municipalities analyzed. Studies have shown that irregular supply of food, inadequate hygiene and sanitary conditions, and lack of farmers or coordination between sectors are the major factors affecting the purchase of food from family farms [34][35][36][37][38]. On the other hand, over the years, municipalities have been able to overcome such barriers and increase the acquisition of food from family farms [34,36,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The availability of food from family farms was highlighted as one of the major criteria in 5 of the 21 municipalities analyzed. Studies have shown that irregular supply of food, inadequate hygiene and sanitary conditions, and lack of farmers or coordination between sectors are the major factors affecting the purchase of food from family farms [34][35][36][37][38]. On the other hand, over the years, municipalities have been able to overcome such barriers and increase the acquisition of food from family farms [34,36,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Esta situação contraria as diretrizes e os objetivos do PNAE, no sentido de fortalecer os Circuitos Curtos de comercialização, favorecer a inclusão social e o desenvolvimento local (Aguiar & Calil, 2018;Alexandre et al, 2016;Gonçalves et al, 2015). Esse achado pode estar associado à falta de conhecimento dos agricultores sobre a CP, visto que não houve publicização nos dois primeiros anos de análise; aos aspectos burocráticos exigidos para acesso dos produtores ao programa, bem como, a falta de preparo técnico dos órgãos e atores responsáveis pela elaboração das CP e ao desconhecimento destes acerca das condicionalidades legais (Castellani et al, 2017;Gregolin, Santos, Felippini, Mateus & Christoffo, 2017;Rockett et al, 2019;Triches, Simonetti, Cessarino, Baccarin & Teo, 2019).…”
Section: Seleção E Priorização Dos Projetos De Vendaunclassified
“…Destaca-se que inicialmente era o propósito do presente estudo proceder uma correlação do percentual de aplicação dos recursos do PNAE na aquisição de gêneros alimentícios da AF com a modalidade de gestão do PNAE. Não obstante, somente oito (26,6%) dentre os 30 artigos totais analisados, fizeram referência a modalidade de gestão (centralizado, descentralizado, semidescentralizado, misto ou terceirizado) (Brito, Pereira & Santos, 2018;Dorneles et al, 2019;Leitão & Bernadino, 2018;Machado et al, 2018;Rodrigues et al, 2017;Rockett et al, 2019;Sodré & Salamoni, 2016;Souza & Vilar, 2019) e 22 (73,3%) não mencionaram essa informação, inviabilizando a análise.…”
Section: Anounclassified
“…Esses resultados podem estar associados ao fato da região Norte ter um número inferior de estabelecimentos rurais da AF (IBGE, 2017), quando comparada com as regiões Nordeste, Sudeste e Sul (Figura 2). Nesta região também chama a atenção o tamanho da área de produção da agricultura não familiar em detrimento da área de produção familiar, a qual apresenta tamanho duas vezes menor, o que pode dificultar com que os agricultores familiares forneçam seus gêneros de forma regular e permanente ao PNAE (Castellani et al, 2017;Rockett et al, 2019;Saraiva et al, 2013;Sodré & Salamoni, 2016;Toyoyoshi et al, 2013).…”
unclassified
See 1 more Smart Citation